Clinical Case of Bilateral Mandibular Auto Transplantation for Missing Bilateral First Molars: Case Report and Review of Literature - Taichi Kasuga; Samito Yamazaki; Hideo Yamazaki; Kouhei Shinmyouzu (Journal of Dentistry And Oral Implants, 2021)
Auto transplantation is a fast and economical option when a suitable donor tooth is available for replacement of a tooth considered impossible to treat. The purpose of this case report is to describe methods used for autotransplantation and its advantages for cases with a missing bilateral mandibular firstmolar, as compared with a dental implant, removable partial denture, and other methods of prosthesis. In the present patient who underwent auto transplantation, clinical and radiographic outcomes were considered satisfactory at one and two years postoperatively. Bone healing was observed around the roots of transplanted teeth, which showed good function. In autotransplantation cases, even when the donor tooth has complete root formation, a high success rate can be achieved when the patient is properly selected and treated. Although the chance of root resorption remains because of necrotic pulp and periodontal irritation during manipulation, auto transplantation should be considered as a good treatment modality in feasible cases. Based on the present findings, even though autotransplantation is not common in general dental practice, we consider that it offers a clinically and economically viable alternative as compared to other more complicated prosthetic and dental implant treatments. The purpose of this report is to show that auto transplantation is a superior treatment method for single molar defects as compared to other prosthetic methods, as the periodontal ligament of the patient can be used and cutting adjacent teeth is avoided. In addition, it is a treatment method that can effectively utilize a wisdom tooth.
Keywords: Auto transplantation